Traumatic Diaphragmatic Hernia - Musa, Nurashidah; Xavier, Ruben Gregory (IIUM Medical Journal Malaysia, 2019)
Traumatic diaphragmatic hernia (TDH) is uncommon and it can be a result from both blunt and penetrating trauma. About to 1% to 7% of patients with blunt trauma sustained TDH. Left sided traumatic diaphragmatic hernia are much common compared to right side.TDH can present acutely or delayed with signs of respiratory distress of intestinal obstruction. The diagnosis was made with the aid of chest radiograph and computed topography (CT) abdomen. A coiled nasogastric tube within the hemithorax is a pathognomonic for TDH. We are presenting a case of high impact injury resulting in a TDH in a 19-year-old, malay male with unsure mechanism injury. He presented with generalised abdominal pain and in respiratory distress with a clinical evidence of abdominal tenderness and type 1 respiratory failure. Subsequently, he underwent exploratory laparotomy and repair of left diaphragmatic hernia. Intraoperatively, noted large linear tear of left hemidiaphragm posterolaterally extending medially until the insertion of falciform ligament. Stomach, left lobe of liver, spleen and splenic flexure of colon were herniated into the left hemithorax. The left diaphragmatic tear was repaired in 2 layers using prolene. A left subdiaphgramatic drain and a chest tube were inserted. Post operatively, the patient was nursed in ICU and recovered well. Repeated chest x -ray showed left lung was fully expanded. With aggressive chest physiotherapy and incentive spirometry, he recovered well and was discharged home. In trauma, there should be a high index of suspicion in patients with both respiratory and abdominal symptoms. Conclusion: Prompt recognition and early definitive management can improve patient outcomes.